Active media : Formation and optical properties of IR photoluminescence centres in bismuth-containing aluminophosphate glass. (31st October 2020) - Romanov, A N; Haula, E V; Korchak, V N
Abstract: We have prepared aluminophosphate glass samples differing in bismuth oxide content and demonstrating broadband near-IR photoluminescence. Analysis of their photoluminescence spectra leads us to conclude that they contain two main types of emission centres, one of which seems to be a bismuth monocation and the other is a cluster ion. In addition to these luminescence centres, the aluminophosphate glasses contain a nonluminescent bismuth-containing centre responsible for the broad, strong optical absorption band peaking at 450 nm.